2001
DOI: 10.1103/physrevlett.86.2601
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Confirmation of the Predicted Shallow Donor Hydrogen State in Zinc Oxide

Abstract: We confirm the recent prediction that interstitial protium may act as a shallow donor in zinc oxide, by direct spectroscopic observation of its muonium counterpart. On implantation into ZnO, positive muons--chemically analogous to protons in this context--form paramagnetic centers below about 40 K. The muon-electron contact hyperfine interaction, as well as the temperature and activation energy for ionization, imply a shallow level. Similar results for the cadmium chalcogenides suggest that such shallow donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
239
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 430 publications
(258 citation statements)
references
References 10 publications
16
239
3
Order By: Relevance
“…While hydrogen can be difficult to directly assess spectroscopically, the well-defined creation and decay properties of muons has led to significant success in the use of µSR as a spectroscopic probe of isolated defect centres in semiconductors that differ from hydrogen only by a mass factor (m Mu /m H ≈ 1/9) and the associated small difference in zero-point energy [85]. While µSR studies of conventional semiconductors such as Si [86] or GaAs [87] found charge transition levels for muonium lying deep within the band gap, as would be expected for the conventional behaviour of hydrogen in these materials, such measurements [84] provided the first spectroscopic evidence of the donor-nature of hydrogen in ZnO, summarized in Fig. 5.…”
Section: Donor Nature Of Hydrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…While hydrogen can be difficult to directly assess spectroscopically, the well-defined creation and decay properties of muons has led to significant success in the use of µSR as a spectroscopic probe of isolated defect centres in semiconductors that differ from hydrogen only by a mass factor (m Mu /m H ≈ 1/9) and the associated small difference in zero-point energy [85]. While µSR studies of conventional semiconductors such as Si [86] or GaAs [87] found charge transition levels for muonium lying deep within the band gap, as would be expected for the conventional behaviour of hydrogen in these materials, such measurements [84] provided the first spectroscopic evidence of the donor-nature of hydrogen in ZnO, summarized in Fig. 5.…”
Section: Donor Nature Of Hydrogenmentioning
confidence: 99%
“…Cox et al [84] performed muon spin rotation and relaxation spectroscopy (µSR) measurements on ZnO, investigating muonium (Mu = [µ + , e − ]) as a lightisotope analogue of hydrogen. While hydrogen can be difficult to directly assess spectroscopically, the well-defined creation and decay properties of muons has led to significant success in the use of µSR as a spectroscopic probe of isolated defect centres in semiconductors that differ from hydrogen only by a mass factor (m Mu /m H ≈ 1/9) and the associated small difference in zero-point energy [85].…”
Section: Donor Nature Of Hydrogenmentioning
confidence: 99%
“…1,2 However, several experimental studies have shown that the dominant native shallow donor in ZnO is hydrogen, as predicted by calculations. [3][4][5] One of the major efforts in semiconductor technology during the recent years was the realization of ptype conductivity in ZnO, leading to optoelectronic devices in the blue spectral range like high-power light-emitting diodes. It is required to suitable compensate the incorporated defects in ZnO resulting in highly resistive material even at high dopant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…A particularly relevant case is the doping character of H in semiconductors and oxides [3][4][5][6], where practically all calculations refer to the electronic structure of H whereas most experimental information comes from μSR [7][8][9][10][11][12][13]. Overlapping data exist only for ZnO where proton-ENDOR (electron-nuclear double resonance) data [14] can be compared directly with μSR results [15][16][17][18]. A number of properties (e.g., ionization energy) are indeed similar for the two species.…”
mentioning
confidence: 99%